Potencial e lacunas de produtividade em milho no Rio Grande do Sul - Ribeiro, Bruna San Martin Rolim (2021)
The objectives of this study were (i) to estimate the yield potential (Yp), water-limited yield potential (Yw) and the yield gap (Yg) of the maize in Brazil, (ii) to estimate how much Brazil still can increase maize production without sustainably increasing the cultivated area (iii) estimate the yield potential and water-limited yield potential in maize crop systems in the state of Rio Grande do Sul (RS) (iv ) identify the biophysical and management factors that potentially explain the yield gap in maize crops in the state of RS. For potential estimates, we calibrated and validated the Hybrid Maize model with data from experiments carried out under potential conditions, with a wide range of climatic conditions, soil types, sowing dates and cycles of the most used cultivars in Brazil. The model calibration was efficient in simulating the development stages and corn yield, which allowed the estimation of yield potential for the predominant production systems in Brazil. To identify the management factors that potentially explain the existing productivity gaps, we used data reported by farmers (2017 – 2019). The main results of this work were: (i) the average Yp and average Yw potential of maize in Brazil is 14.3 Mg ha-¹ and 10.9 Mg ha-¹; (ii) water and management are responsible for 24 and 45% of the maize yield gap in Brazil; (iii) it is possible to have a productive increase of 27 Mt of maize in the current arable area and avoid the destruction of 4.3 million ha of forests in Brazil; (iv) the highest yield potential in the state of RS was found in the system characterized by one cultivation per summer crop, with planting before September 20 and use of cultivars with super-early cycle (v) the maize yield gap in RS can be reduced by improving management practices such as: planting before September 20, crop rotation, increase in plant density and use of cultivars with hyper and super-early, and (vi) RS has the potential to increase production of 3 Mt without increasing the cultivated area, only with good management practices it can become self-sufficient in maize production. This information can help optimize current corn management practices to increase yield and resource efficiency.